Rhetorical Uses of Spice On East London Indian Food Tours - Shultz, Sarah (Ethnologies, 2023)
This article provides an ethnographic account of an Indian food tour that runs along Brick Lane, a street famous for its Indian restaurants in east London. The tour is discussed in the context of Indian cuisine’s history in the United Kingdom and the construction of Brick Lane as a culinary tourist attraction. Uses for the concept of spice in the tour text, as an indicator of both heat and richness of flavor, are analyzed. It is found that spice is used to persuade tour participants that they are having an out of the ordinary experience in keeping with current trends in gourmet and culinary tourist discourses. At the same time, interviews with tour guides and the tour organizer suggest they employ the concept of spice in ways that can seem at odds with the text of the tour. Spice emerges as a tool for achieving diverse commercial and personal goals.